Thermodynamic responses of bleed air on separated flow high by-pass turbofan engine under constant speed and constant thrust cases - Aygun, Hakan (Pergamon-Elsevier Science Ltd, 2024)
Gas turbine engines, especially turbofan, have been famous for their fuel economy and reliability attributes. Therefore, these have continued to be manufactured by updating their features. Therefore, thermodynamic analyses related to turbofan engines have drawn great attention, providing deeper insight into potential improvements. New generation aircrafts have been conceived to draw bleed air as little as possible from their aeroengines so as to provide lower fuel consumption. In this study, influences of bleed air ratio (BAR) ranging from 1 % to 6 % on high by-pass turbofan (HBT) engine are handled by considering constant speed (CS) and constant thrust (CT) cases. Specific fuel consumption of HBT engine changes between 20.68 g/kN and 22.25 g/kN at CT whereas varies between 20.63 g/kN and 21.9 g/kN at CS owing to variation of BAR. Moreover, exergy efficiency of HBT resides between 26.92 % and 25.02 % at CT while changes 26.99 % and 25.43 % at CS. It shows that to maintain thrust constant could slightly penalty the engine performance in terms of fuel efficiency. On the other hand, the higher BAR leads to lower exergy efficiency of the combustor, which changes 80.95 %-82.33 % ranges at CT and varies 80.77 %-82.31 % intervals at CS. Finally, improvement potential rate for the combustor is found higher 1 MW and increases with elevated BAR whereas that for other five components is measured less than 0.04 MW. It could be underscored that adverse effect of BAR for both cases is observed. It is thought that this study helps in observing what extent the engine is affected from usage of bleed air in terms of thermodynamic metrics.
Keywords: Bleed air; Thrust; Turbofan; Exergy; Efficiency